Ragam Bahasa dan Dinamika Penggunaan Bahasa Serapan pada Bahasa Indonesia di Kalangan Mahasiswa dalam Bermedia Sosial (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Digital technology has influenced the way students interact, especially through a number of social networking platforms. This transformation triggers the development of a new, adaptable, and continuous way of communicating. This research explores various types of language used by students in daily activities and on social media, as well as researching how assimilated words play a role in the evolution of language patterns in the digital age. This research focuses on three main aspects: variations in language forms that appear in student interactions, the use of absorption words in each type of language, and factors that encourage changes in the use of absorption words among students. The methodology applied is qualitative descriptive, with data collection through content review on social media and relevant literature studies. The results of the study show that students apply various language styles, from formal to casual, including the use of slang, and all of this is influenced by the context of online communication they live. Absorption words adopted by students on social media platforms act as a means to express their identity, help them adapt in a global environment, and speed up interaction between friends. The practice of language use by students is influenced by various social and religious factors in the context of digital culture, as well as the demand to communicate faster and more efficiently, coupled with their exposure to foreign languages. Overall, this study concluded that the relationship between various forms of language and its practice of use, along with changes in norms regarding what is considered appropriate, forms a new communication style that reflects the development of the Indonesian language among students on social media. This finding is expected to contribute to the latest research and enrich the discussion about the ongoing language dynamics.